Anthropogenic Nest Materials May Increase Breeding Costs for Urban Birds - Suárez-Rodríguez, Monserrat; Montero-Montoya, Regina D.; Macías Garcia, Constantino (Frontiers in Ecology and Evolution, 2017)
Even in socially monogamous species, sexual conflict is one reason that often promotes differences in the roles of sexes during reproduction, which may lead to one sex making a disproportionate contribution, and thus incurring disproportionate costs, at particular moments of the breeding process. In Mexico City, a number of songbird species line their nests with fibers from discarded cigarette butts, which reduce ectoparasite load but are genotoxic. As male Passer domesticus make substantial contributions to nest building whereas male Carpodacus mexicanus do not contribute to nest building, we hypothesized that the toxic effects of exposure to cigarette butts should be greater for females C. mexicanus than for conspecific males, but that there should be little or no difference in P. domesticus. As expected there was more exogenous genotoxic damage in the red-blood cells of incubating female C. mexicanus the more cigarette butts were found in their nest, and much more than in their conspecific males. Damage in males was not associated to cigarette butts; it was initially lower than in females, but it increased near fledging, together with their breeding effort. In both male and female P. domesticus, however, genotoxic damage was equally apparent and greater the more cigarette butts were in the nest. The novel use of a toxic, anthropogenic parasite repellent by urban birds may be thus asymmetrically increasing the breeding costs paid by the member of the pair most involved in nest building and incubation.